THE EFFECT OF SOCIAL SECURITY ON EMPLOYEE PERFORMANCE WITH WORK MOTIVATION AS AN INTERVENING VARIABLE (Case Study on Employees of United Kongdom Medical Dcotor and Nurses) - Maurizio Zanardi; Stephen Martin (PT. Radja Intercontinental Publishing, 2020)
In this study the population was Employees of United Kongdom Medical Dcotor and Nurses, namely as many as 950 people. From the basis for determining the writer's sample based on the Slovin formula with an error tolerance of `10%, the number for the sample is 91 respondents. the first hypothesis is accepted, meaning that location accessibility (X) has a significant effect on community satisfaction (Y1). the second hypothesis is rejected, meaning that location accessibility (X) has no significant effect on community satisfaction (Y2). the third hypothesis is accepted, meaning that service quality (Y1) is an intervening variable that mediates the effect of location accessibility (X) on community satisfaction (Y2).